An Insight into the Mysteries of Learning Hungarian as a Foreign Language - Katalin Hnatyk; Гнатик Каталін; Hnatik Katalin (Вид-во МДУ, 2018)
Abstract. The article tries to gather the main difficulties of foreign language learning related to Hungarian as a target language. It also tries to examine the myth of Hungarian language learning. Comparing the problems of studying Hungarian and difficulties of foreign language learning we can find several similarities. Researches investigating the main difficulties of foreign language learning show that the negative language transfer cause a lot of problems. It is held to be responsible for foreign accents, the mistakes in using inflection or wordorder. Applied linguists concentrate more on negative transfer than on positive transfer. Cultural differences also cause problems in foreign language learning.
Keywords: foreign language; foreign language difficulties; myth